Combined effects of solute drag and Zener pinning on grain growth of a NiCoCr medium-entropy alloy. (September 2021) - Hu, G.W.; Zeng, L.C.; Du, H.; Wang, Q.; Fan, Z.T.; Liu, X.W.
Abstract: Coarse grains are formed during thermomechanical processing for the widely studied NiCoCr medium-entropy alloy (MEA) due to the lack of effective approaches to restrain grain growth. Here, a novel integrated method combing solute drag and Zenner pinning effects are proposed. The 0.5 at.% C was added to precipitate carbides which generates pinning of the grain boundaries; while solute drag is implemented by 3 at.% addition of Mo with low self-diffusion coefficient. Results show that most of Mo is dissolved in the matrix and M23 C6 carbides uniformly precipitated after aging. The combined method shows a significant effect on controlling grain growth and results in much finer equiaxed grains. A very high growth activation energy of 511 kJ / mol was obtained, double that of NiCoCr MEA (251 kJ / mol ). This work shows that the grain growth kinetics of the NiCoCr based MEA during traditional thermomechanical processing can be tuned by adjusting carbide precipitates and selecting appropriate solute elements. Highlights: M23 C6 carbides in NiCoCr were obtained by microalloying with Mo and C. Solute Mo and carbides show solute-drag and Zener pinning effect, respectively. Combined effects of solute drag and Zener pinning result in much finer grains. The growth activation energy is 511 kJ / mol, double that of NiCoCr MEA.